2022
DOI: 10.1021/acsami.2c16286
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Superlow Friction in Strengthening Si-DLC/PLC Nanostructured Multilayer Films for Robust Superlubricity at Ultrahigh Contact Stress

Abstract: Diamond-like carbon (DLC) films have significant potential to provide solutions for the friction reduction and the lubricity problem of mechanical moving friction pairs. However, the realization of excellent lubrication or even superlubricity and long lifetime under heavy loading conditions is still a great challenge, which is crucial for the applications of DLC in harsh environments. Here, we construct a group of property-strengthening Si-DLC/PLC multilayer films that could withstand ultrahigh contact stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For samples NLSA-P 2222 , NLSA-TEOA, and NLSA-CHOH, their extreme pressure can reach over 750 N; in particular, the load-bearing pressure of NLSA-CHOH can be up to 850 N. Structurally, the extreme pressure elements N, P, and S in the IL structure will be favorable to the exceptional load-bearing capacity, whose more detailed analysis is the coordination bonds formed between IL and the empty orbits of metals. 42 Among them, the N element is adsorbed to the surface through its lone pair electrons forming a coordination bond with the empty orbitals of the metal in the friction process. Also, the N element in the anion may be adsorbed to the positively charged metal surface by the electrostatic effect, while the weaker C−S bonds in the molecule will tend to form a reactive film that played the antiwear role.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For samples NLSA-P 2222 , NLSA-TEOA, and NLSA-CHOH, their extreme pressure can reach over 750 N; in particular, the load-bearing pressure of NLSA-CHOH can be up to 850 N. Structurally, the extreme pressure elements N, P, and S in the IL structure will be favorable to the exceptional load-bearing capacity, whose more detailed analysis is the coordination bonds formed between IL and the empty orbits of metals. 42 Among them, the N element is adsorbed to the surface through its lone pair electrons forming a coordination bond with the empty orbitals of the metal in the friction process. Also, the N element in the anion may be adsorbed to the positively charged metal surface by the electrostatic effect, while the weaker C−S bonds in the molecule will tend to form a reactive film that played the antiwear role.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The extreme load test (Figure f) found that the COFs of the IL water-based lubricating system were maintained at a stable and low level (less than 0.15). For samples NLSA-P 2222 , NLSA-TEOA, and NLSA-CHOH, their extreme pressure can reach over 750 N; in particular, the load-bearing pressure of NLSA-CHOH can be up to 850 N. Structurally, the extreme pressure elements N, P, and S in the IL structure will be favorable to the exceptional load-bearing capacity, whose more detailed analysis is the coordination bonds formed between IL and the empty orbits of metals . Among them, the N element is adsorbed to the surface through its lone pair electrons forming a coordination bond with the empty orbitals of the metal in the friction process.…”
Section: Resultsmentioning
confidence: 99%